Pengaruh Minat dan Peran Guru terhadap Peningkatan Membaca Al-Qur’an Siswa - Sakdiah (Getpress Management Journals, 2025)
This study aims to determine the effect of Qur'an Hadith teacher efforts on student interest in learning at Madrasah Aliyah Muallimin UNIVA Medan. The focus of the study is directed at the extent to which the teacher's active role in the learning process is able to arouse students' interest and enthusiasm in participating in Qur'an Hadith lessons. The method used in this research is a quantitative approach with data collection techniques through an open questionnaire. The research sample amounted to 35 students who were selected purposively. The research instrument was analyzed using a Likert scale, and the data were processed through the stages of validity test, classical assumption test, determination test, and partial hypothesis test (t test) with the help of the SPSS version 26 program. The results showed that the efforts of the Qur'an Hadith teacher had a significant and positive influence on student interest in learning. This is evidenced by the r-count value of 6.705 which is greater than the r-table of 1.660. In addition, the amount of influence shown by the coefficient of determination reaches 61.4%, which means that most of the variation in student interest in learning can be explained by the teacher effort variable. These results underscore the need to strengthen teachers' pedagogical competence, especially in religious subjects.